PROTECTIVE EFFECTS OF ANNONA MURICATA LINN. (ANNONACEAE) LEAF AQUEOUS EXTRACT ON SERUM LIPID PROFILES AND OXIDATIVE STRESS IN HEPATOCYTES OF STREPTOZOTOCIN-TREATED DIABETIC RATS - Adewole, Stephen O.; Ojewole, John A. O. (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
Extracts from various morphological parts of Annona muricata Linn. (Annonaceae) are widely used medicinally in many parts of the world for the management, control and/or treatment of a plethora of human ailments, including diabetes mellitus (DM). The present study was undertaken to investigate the possible protective effects of A. muricata leaf aqueous extract (AME) in rat experimental paradigms of DM. The animals used were broadly divided into four (A, B, C and D) experimental groups. Group A rats served as ‘control’ animals and received distilled water in quantities equivalent to the administered volumes of AME and reference drugs’ solutions intraperitoneally. Diabetes mellitus was induced in Groups B and C rats by intraperitoneal injections of streptozotocin (STZ, 70 mg kg-1). Group C rats were additionally treated with AME (100 mg kg-1 day-1, p.o.) as from day 3 post STZ injection, for four consecutive weeks. Group D rats received AME (100 mg kg-1 day-1 p.o.) only for four weeks. Post-euthanization, hepatic tissues were excised and processed biochemically for antioxidant enzymes and lipid profiles, such as catalase (CAT), reactive oxygen species (ROS), glutathione (GSH), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), thiobarbituric acid reactive substances (TBARS), triglycerides (TG), total cholesterol (TC), high density lipoprotein (HDL) and low density lipoprotein (LDL), respectively. Treatment of Groups B and C rats with STZ (70 mg kg-1 i. p.) resulted in hyperglycaemia, hypoinsulinaemia, and increased TBARS, ROS, TC, TG and LDL levels. STZ treatment also significantly decreased (p<0.05) CAT, GSH, SOD, GSH-Px activities, and HDL levels. AME-treated Groups C and D rats showed significant decrease (p<0.05) in elevated blood glucose, ROS, TBARS, TC, TG and LDL. Furthermore, AME treatment significantly increased (p<0.05) antioxidant enzymes’ activities, as well as serum insulin levels. The findings of this laboratory animal study suggest that A. muricata extract has a protective, beneficial effect on hepatic tissues subjected to STZ-induced oxidative stress, possibly by decreasing lipid peroxidation and indirectly enhancing production of insulin and endogenous antioxidants.